Linguistic Analysis of Unplanned Discourse in David Sedaris “Calypso” - Binin Mustafa Saeed; Rozgar Yousif Omar (Zanco Journal of Humanity Sciences)
This study aims to investigate the linguistic features that distinguish spontaneous and informal communication between individuals, often known as unplanned discourse. This study thoroughly examines a range of grammatical features and patterns seen in conversational discourse. The study analyzes the distinctive grammatical structures and phenomena that develop in unplanned discourse by studying a wide range of conversational data from different scenarios, dialogues, and casual conversations found in David Sedaris' Calypso. The study takes a qualitative approach, employing linguistic analysis techniques to discover recurrent patterns and syntactic variations contributing to spontaneous conversational discourse's overall order and coherence. The findings emphasize the informality, flexibility, unfinished utterances, and dynamic nature of grammatical usage in conversations, as seen by the inclusion of colloquial expressions, and digressions. The research adds to our understanding of how language is used in everyday interactions by throwing light on the various grammatical elements that distinguish conversational speech and their significance in supporting efficient communication. The findings of this study can be used to improve language teaching approaches and discourse analysis frameworks, as well as to contribute to the development of linguistic theories about unplanned discourse.